Improvement of Student Achievement Through Problem Based Differentiated Learning - Wahyu Ma’ruf Dharmaji; Rina Astuti* (Universitas Syiah Kuala, 2023)
Learning needs to accommodate the diversity of students through innovative selection of strategies or learning models that are oriented towards an independent learning curriculum. The learning model that can be applied is through differentiated problem based learning (PBL) which can meet students' learning needs. This study aims to determine the increase in student learning outcomes using a differentiated PBL model. This research uses a type of qualitative research with a descriptive approach. Sampling was carried out using the purposive sampling technique, namely the technique of determining the sample with certain considerations. Data collection techniques using tests and observation sheets. Data analysis techniques used the normality test and paired sample t-test and used the formula on the observation sheet. The results showed that learning using the differentiation model with PBL increased significantly by 83.75 and the learning process took place effectively by 78